Impact of Brachiaria decumbens leaf meal supplementation on broiler chickens raised in tropical environments in terms of growth performance, blood biochemistry, and stress biomarkers - Chung, Eric Lim Teik; Alghirani, Mohamed M.; Abu Kassim, Nafeesa; Ong, Yee Lyn; Jesse, Faez Firdaus Abdullah; Sazili, Awis Qurni; Loh, Teck Chwen (Fundacao APINCO de Ciencia e Tecnologia Avicolas, 2024)
This study's main objective was to determine the novel impact of supplementing Brachiaria decumbens leaf meal on the growth performance, blood biochemistry, and stress biomarkers of commercial broilers raised in hot and humid environments. A total of 300 male Ross 308 day-old broilers were divided into six different treatment groups at random. In Treatment 1, commercial diets without any additional additives were given to broilers. In Treatment 2, broilers were fed commercial diets containing 100 mg/kg of the antibiotic oxytetracycline. Similar commercial diets supplemented with 25, 50, 75, and 100 mg/kg of B. decumbens leaf meal, respectively, were given to Treatments 3, 4, 5, and 6 without the use of antibiotics. Growth performance, serum lipid profile, acute phase proteins, hormone, and heat shock protein all differed significantly (P < 0.05) among the treatments. The greatest final body weight, body weight gain, and lowest feed conversion ratio were generally seen in T3 broilers supplemented with 25 mg/kg of B. decumbens leaf meal. Besides, T3 broilers supplemented with 25 mg/kg of B. decumbens leaf meal showed the lowest AGP, corticosterone, and HSP 70 concentrations, while T6 broilers treated with 100 mg/kg of B. decumbens leaf meal had the lowest LDL and highest HDL values. The results of this study clearly demonstrate that supplementing broilers with B. decumbens leaf meal only requires a small amount to improve growth and reduce the effects of stress, but that a higher concentration is necessary to improve lipid profiles.